CT Analysis of Inflammatory Lesions of Paranasal Sinuses - Shukla, Bharvi A; Shilpa J Parikh (Journal of Orofacial Research, 2023)
Background & aim: Computed tomography (CT) is regarded as the “gold standard” in the primary imaging of inflammatory sinonasal lesions. The present study was conducted with the aim to perform a CT analysis of inflammatory lesions of paranasal sinuses. Material method: A cross-sectional radiographic study was conducted among randomly selected 156 CT scans that have been collected from patients who are clinically and radiographically diagnosed with paranasal sinus pathologies. However, 58 scans were excluded due to various reasons like presence of trauma, poor quality images etc and so 98 scans were further assessed. Results: Paranasal sinus pathologies were found to be most prevalent in the age group of 46-60 years affecting males more than females. The maxillary sinus was the most commonly affected. The most common sinus pathology was reported to be mucormycosis (fungal sinusitis) and the pathologies were found to be present more bilaterally. Conclusion: Paranasal sinus pathologies may mimic symptoms of orofacial pain. Thus dentists in general and oral physician in particular should not overlook sinus diseases as the cause of dental and facial pain. Also, a careful and thorough investigation can detect anatomical variations and pathoses that affect the maxillofacial area. Hence, it is imperative for an oral radiologist to have knowledge of the same.